Mediating Meaning-Making: The Process of Symbolic Action in Transformative Pedagogy - Olga V. Kritskaya; John M. Dirkx (Adult Education Research Conference, 2000)
Conditions for fostering transformative learning within the formal learning setting were examined. The paper focused on the role of the text and the use of symbols and images in construction of meanings associated with the content being studied.